2016
DOI: 10.3961/jpmph.16.020
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Disposal of Child Faeces: A Community-based Study in a Rural Block in West Bengal, India

Abstract: ObjectivesA clean India is the responsibility of all Indians. One of the objectives of the Swachh Bharat Abhiyan (Clean India Initiative) is to bring about behavioural changes regarding healthy sanitation practices. While large-scale programs in India have increased latrine coverage, they have to some extent failed to bring behavioural changes ensuring optimal latrine use, including the safe disposal of child faeces, which is a significant source of exposure to faecal pathogens. Hence, this study was done to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 8 publications
9
32
5
Order By: Relevance
“…This notwithstanding, nearly half of the households with improved toilet facility practiced unsafe disposal of children’s stool, suggesting that the availability of improved toilet facility does not guarantee safe disposal of children’s faeces. Some previous studies [ 12 , 13 , 31 ] made a similar observation. Allied with these studies is our finding that households with unimproved water supply have lower likelihood of disposing of children’s faeces unsafely.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This notwithstanding, nearly half of the households with improved toilet facility practiced unsafe disposal of children’s stool, suggesting that the availability of improved toilet facility does not guarantee safe disposal of children’s faeces. Some previous studies [ 12 , 13 , 31 ] made a similar observation. Allied with these studies is our finding that households with unimproved water supply have lower likelihood of disposing of children’s faeces unsafely.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies in India [ 12 , 13 ], Bangladesh [ 14 ], Nigeria [ 15 ], Burkina Faso [ 16 ], and Ethiopia [ 17 ] have revealed positive associations between disposal of children’s stool, and individual/maternal and contextual/household factors. These studies have shown that women with high wealth status, those with higher levels of education [ 15 , 16 ], women who live in urban areas [ 17 ], and those who have access to improved toilet facility [ 12 , 17 , 18 ] are more likely to safely dispose of children’s stool.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggests that location of water source is associated with unsafe child feces disposal practice in West Bengal India (Preeti, Sahoo, Biswas, & Dasgupta, 2016). However, this study did not find it statistically significant.…”
Section: Environmental Variablescontrasting
confidence: 85%
“…Moreover, more educated mothers were observed to be less likely to practice unsafe disposal of child feces. Previous findings confirm this association (Azage & Haile, 2015;Preeti et al, 2016). Having more education can improve one's ability in accessing and obtaining information of many types, including information on hygienic practices.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 57%
See 1 more Smart Citation